The real value of house prices: what the cost of accommodation can tell policymakers - Lyons, Ronan C. (Statistical and Social Inquiry Society of Ireland, 2012)
This paper explores the potential for the housing market to inform public policy in Ireland by developing a model of the determinants of the cost of accommodation. It does this by using a rich dataset of sales and lettings accommodation costs in Ireland over the period 2006-2010. A large empirical literature has grown up around a core concept that households pay to enjoy particular amenities. Five categories of amenity are included in the analysis: market depth, transport, human capital, social capital and environmental amenities. The typical amenity included is found to have a significant effect on accommodation costs, one that is larger in the sales segment than in the rental segment. Differences by amenity type highlight the importance of using ?supply-side variation? to ensure the robustness of estimates of private benefit from public goods.
read before the Society, 15 March 2012
Keywords: housing markets; housing prices; hedonic regression; 314.15